Waste Valuation and Problems Encountered In Waste Bank Management: A Case Study at BSU ASRI BMP - Asmoro Lelono; Nur Asyia Alfiyani; Rini Nur Intani (Faculty of Mathematics and Natural Sciences, University of Jember. Jl. Kalimantan No.37, Krajan Timur, Jemberlor, Kec. Sumbersari, Jember Regency, East Java 68121, 2023)
Community participation-based waste management has been carried out by DKLH Jember Regency through the establishment of the Main Waste Bank its derivative organization, namely the Unit Waste Bank at a lower level. In this system, the effort being made is the integration of waste management, starting from the household as a producer, followed by sorting, then depositing it to BSU and ending with delivery to a temporary warehouse so that the waste is handled properly. This article aims to explore the potentials and problems encountered in the management of a Waste Bank which involves the participation of residents while still paying attention to aspects of economic feasibility. The research was carried out using the analitcal descriptive via interview and analysis of primary data owned by BSU ASRI BMP with due observance of scientific principles and maintaining the independence and interests of the authors. From the results of the research it is known that waste valuation efforts by providing economic value to each component of waste produced by each household are able to generate citizen interest in sorting and depositing the waste produced. The main contributors in the transfer of inorganic waste from BSU to BSI sequentially are paper, plastic and metal waste with the highest exchange rate ratio in metal waste. The main problem faced in the management of waste banks is the motivation of residents to independently handle daily waste. Besides that, there are also management constraints because the managers are housewives who must divide their time and attention for routine daily activities.